The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2214/ajr.12.10187
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Computer-Aided Detection Systems on Radiologist Accuracy With Digital Mammography

Abstract: OBJECTIVE The purpose of this study was to assess the impact of computer-aided detection (CAD) systems on the performance of radiologists with digital mammograms acquired during the Digital Mammographic Imaging Screening Trial (DMIST). MATERIALS AND METHODS Only those DMIST cases with proven cancer status by biopsy or 1-year follow-up that had available digital images were included in this multireader, multicase ROC study. Two commercially available CAD systems for digital mammography were used: iCAD SecondL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 22 publications
(24 reference statements)
2
34
0
Order By: Relevance
“…A meta-analysis in 2008 of 10 studies of CAD applied to screening mammography concluded that CAD significantly increased recall rate with no significant improvement in cancer detection rates compared to readings without CAD (37). The largest recent reader study of digital mammography obtained during the Digital Mammography Imaging Screening Trial (DMIST) found no impact of CAD on radiologist interpretations of mammograms (5). In that report, the authors concluded that radiologists overall were not influenced by CAD markings and CAD had no impact, either beneficial or detrimental, on mammography interpretations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis in 2008 of 10 studies of CAD applied to screening mammography concluded that CAD significantly increased recall rate with no significant improvement in cancer detection rates compared to readings without CAD (37). The largest recent reader study of digital mammography obtained during the Digital Mammography Imaging Screening Trial (DMIST) found no impact of CAD on radiologist interpretations of mammograms (5). In that report, the authors concluded that radiologists overall were not influenced by CAD markings and CAD had no impact, either beneficial or detrimental, on mammography interpretations.…”
Section: Discussionmentioning
confidence: 99%
“…Data were pooled from five mammography registries that participate in the Breast Cancer Surveillance Consortium (BCSC) (20) funded by the National Cancer Institute: (1) San Francisco Mammography Registry; (2) New Mexico Mammography Advocacy Project; (3) Vermont Breast Cancer Surveillance System; (4) New Hampshire Mammography Network; and (5) Carolina Mammography Registry. Each mammography registry links women to a state tumor registry or regional Surveillance Epidemiology and End Results program that collects population-based cancer data.…”
Section: Methodsmentioning
confidence: 99%
“…The normal goal of a CAD system is to direct the radiologist's attention to specific, suspicious locations. Although these systems perform at a level comparable to that of an expert radiologist, they have not been hugely successful in clinical practice (35), in part because the positive predictive value of any given CAD mark is very low in a mammography screening situation where the prevalence of disease is low. As a result, radiologists tend to dismiss the correct CAD marks when they occur (36).…”
Section: Discussionmentioning
confidence: 99%
“…115 In a recent retrospective study, 300 examinations from DMIST 10 were re-read by 15 radiologists using two CAD systems. 116 No significant difference in sensitivity and specificity was found for the group as a whole. 116 CAD is currently being investigated for DBT and may potentially reduce reading times.…”
Section: Breast Density Assessmentmentioning
confidence: 87%
“…116 No significant difference in sensitivity and specificity was found for the group as a whole. 116 CAD is currently being investigated for DBT and may potentially reduce reading times. 117 …”
Section: Breast Density Assessmentmentioning
confidence: 87%